The Effect of Limestone Particle Size on the Performance of Three Broiler Breeder Purelines - Ekmay, R.D.; Coon , C.N. (International Journal of Poultry Science, 2010)
A 40-wk study was conducted to assess the effects of limestone particle size on the production performance, skeletal integrity and Ca/P balance of three broiler breeder purelines. A flock of LINE A, LINE B and LINE C broiler breeders were reared according to Cobb 500 guidelines (Cobb-Vantress, 2005) and transferred to a production house at 21 wks of age. Each line was split into two groups consisting of 66, 68 and 62 hens for the LINE A, LINE B and LINE C lines, respectively and fed a diet that differed only in the inclusion of either large (3489.7 microns; 38.5% solubility) or small particle (185.5 microns; 58.8% solubility) limestone. Production performance, egg quality, breeder skeletal integrity, reproductive performance, progeny performance and Ca/P balance were monitored. LINE B produced the most eggs per hen housed and highest egg number, followed by LINE C and LINE A, respectively. Egg weight, specific gravity and shell weight were also superior in LINE B compared to the other purelines. The % P retention did not differ across purelines, but Ca retention was also highest in LINE B. Breeder skeletal integrity and progeny bone quality were higher in LINE C. The addition of large particle limestone in lieu of small particles did not provide a consistent effect in production performance but significantly improved shell quality (P = 0.0013), bone quality (P = 0.0341). The large genetic differences in purelines compared to parent stock may uniquely alter the effects of particulate calcium on production performance; yet large particle limestone provided the boost in shell quality and bone quality reported by others. In summary, LINE A, LINE B and LINE C purelines utilize Ca and P differently and have unique genetic potential for hatching egg production, egg shell quality, breeder bone ash and progeny bone ash.